The Syntactic Functions of Conversational Implicature Utterances with Academic Context: Pragmasyntactic Studies - Suhartono Suhartono (Script Journal: Journal of Linguistics and English Teaching, 2020)
Background: Pragmatic analysis has been widely developed through the use of an implicature. This paper tries to focus on the syntactical functions elaborated from an academic discourse as the focus of analysis. This study aimed to find the syntactic function of conversational interference spoken by speakers in academic contextual communication. The syntactical functions were identified in three parts: predicate, subject, and adverbs. Methodology: To achieve this objective, data in the form of oral statements with academic background were collected using note-taking techniques from 114 subjects through participant observation in lecture activities, online and offline meetings, discussions, final project consultations, and training. The data was analyzed using the Miles and Huberman flow technique through data reduction, data presentation, and the conclusion/verification of data analysis results. Findings: Results show that pragmatic expressions that can help the speaker to identify the intent of the speaker were positioned as fillers of predicates, subjects, and information. This pragmatic expression is the impact of the incomprehensibility or inconsistency of the narrator with the speaker who was previously the listener. For the sake of completeness, speakers add other pragmatic expressions with substitution strategies, additions, and conditional forms with an orientation that prioritizes politeness by avoiding direct speech with the negation of 'tidak (no),' 'belum (not yet),' 'bukan (not)' and 'jangan (not).